Analisis Work Family Conflict, Stres Kerja Dan Kinerja Wanita Berperan Ganda Pada Yayasan Compassion East Indonesia - Roboth, Jane Y (Universitas Sam Ratulangi)
The research was conducted with the objective of verifying the influence of Work Family Conflict consists of work to family conflict and family to work conflict and with job stress to analyze performance of dual role women in the foundation Compassion East Indonesia. The population in this study was all marriedÂ women who work in the organization of Compassion Indonesia until December 2014, the number of employees 68 with a sample of 30 people. Data analysis using path analysis. The results of the t test for Work-Family Conflict (X1) on the performance of Women Serving Dual (Y) shows the value of 0491 means that sig sig value is greater than the probability value of 0.05 (0.491> 0.05), the conclusion that can be drawn is H0 is accepted and H1 is rejected. The results of the t test for family-work conflict showed sig 0.003 and t indicates the value of 3.112, meaning that the value of sig is smaller than theprobability value of 0.05 (0.003 <0.05), the conclusion that can be drawn is H2 H2 is rejected and accepted. The results of the t test for job stress (X3) on the performance (Y) showed sig 0.000 and t indicates the value of 6.192, meaning that the value of sig is smaller than the probability value of 0.05 (0.000 <0.05), the conclusion that can be drawn is H3, H3 is rejected and accepted.Keywords: Work Family Conflict, Job Stress and Performance Female Employees